MAX WEBER’S THEORY OF LAW EDUCATION AND POLITICAL VIEWS OF RELIGION - Kronis, Ivars; Zarins, Kristaps (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
In order to better evaluate Weber's most popular views on the economic ethics of religion, by comparison and due to the interaction of the opposites and sets of views expressed in them, in this work, the discipline of human rights will also be analysed, which will closely identify Weber's asceticism about the spirit of normative Protestantism and the ethics of capitalism and law school and education. The purpose of the research is to establish and identify the ideas expressed by Weber regarding the value scope of social classes, layers and typology of religion, by analysing them – conventionally, but specifically – through the doctrine of lex nature and education impact in school of sociology. Additionally, the purpose of the present work is to answer what is the general structure of Weber's philosophical thoughts and views on school of law, to find and identify in it the asceticism of the sociology of religion, interspersed with the theory of conflict and domination. But the relevance of the research is rooted in the fact that the methods of Weber's scientific approach are used to analyse the state's institutional and orderly system-theoretical dependence from the bureaucratized forms of public authority and this impact in knowledge.